Tales of Troy and Greece - Lang, Andrew, 1844-1912; Ford, H. J. (Henry Justice), 1860-1941 (Salt Lake City, UT : Project Gutenberg, 2010)
"Tales of Troy and Greece" by Andrew Lang is a collection of retold ancient Greek myths and stories, written in the early 20th century. This volume focuses on the legendary tales surrounding the Trojan War, particularly the adventures of notable heroes such as Ulysses (Odysseus), Achilles, and the conflicts arising from the beauty of Helen. The narratives deliver not only action and adventure but also explore themes of honor, love, and the consequences of war. The opening of the book begins by setting the scene of ancient Ithaca and introducing Ulysses, the son of King Laertes, detailing his upbringing with an emphasis on his bravery and cunning nature. As a boy, Ulysses experiences formative adventures, including a notable encounter with a wild boar, which leaves him with a scar, foreshadowing his future trials. The narrative shifts to portray the vibrant life in Greece during Ulysses' youth, including customs surrounding marriage and the formidable beauty of Helen, which ultimately leads to the legendary conflict of the Trojan War. The introduction establishes the rich historical context and character-driven storytelling that will unfold throughout the tales. (This is an automatically generated summary.)
Ulysses, the sacker of cities -- The wanderings of Ulysses -- The fleece of gold -- Theseus -- Perseus.
The first part of this e-book ("Ulysses the Sacker of Cities") is a duplication of e-book #1973, which ends with the fall of Troy. This e-book includes material not in #1973: the wanderings of Ulysses after the war and his return home, and the stories of the golden fleece, Thesues and Perseus.
Release date is 2010-05-10
E-text prepared by Peter Vickers, Suzanne Shell, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Mythology, Greek; Trojan War -- Literature and the war; Troy (Extinct city) -- Legends